2007
DOI: 10.1091/mbc.e07-05-0517
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Novel Plk1 Inhibitor ZK-Thiazolidinone to Elucidate Functions of Plk1 in Early and Late Stages of Mitosis

Abstract: Polo-like kinase 1 (Plk1) is a key regulator of mitotic progression and cell division in eukaryotes. It is highly expressed in tumor cells and considered a potential target for cancer therapy. Here, we report the discovery and application of a novel potent small-molecule inhibitor of mammalian Plk1, ZK-Thiazolidinone (TAL). We have extensively characterized TAL in vitro and addressed TAL specificity within cells by studying Plk1 functions in sister chromatid separation, centrosome maturation, and spindle assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
175
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(195 citation statements)
references
References 68 publications
(122 reference statements)
16
175
1
3
Order By: Relevance
“…TAL is a thiazolidinone developed by Bayer Schering Pharma that inhibits Plk1 in vitro with an IC 50 of 19 nM. Again, the phenotypes observed in cell based assays are entirely consistent with Plk1 inhibition [41]. Importantly, both BI 2536 and TAL induce a penetrant monopolar spindle phenotype which in turn activates the spindle checkpoint resulting in a mitotic arrest phenotype.…”
Section: Plk1 Inhibitors-more Monopolar Spindlesmentioning
confidence: 79%
“…TAL is a thiazolidinone developed by Bayer Schering Pharma that inhibits Plk1 in vitro with an IC 50 of 19 nM. Again, the phenotypes observed in cell based assays are entirely consistent with Plk1 inhibition [41]. Importantly, both BI 2536 and TAL induce a penetrant monopolar spindle phenotype which in turn activates the spindle checkpoint resulting in a mitotic arrest phenotype.…”
Section: Plk1 Inhibitors-more Monopolar Spindlesmentioning
confidence: 79%
“…They showed the same range of activity to that of purpurogallin with IC 50 values of 102 (1), 128 (2) and 114 (purpurogallin) μM. Several Plk1 inhibitors have been reported including purpurogallin, [6][7][8] however, most of them contain an aromatic moiety in their molecules apart from the structures of 1 and 2, which have a 5,5-spiroacetal core with alkyl chain and tricarboxylic acid moiety. Also 2 has been isolated as an inhibitor of heparanase and the activity has not been investigated in detail.…”
mentioning
confidence: 97%
“…5 Thus, Plk1 is considered to be an attractive target for the treatment of human cancers. [6][7][8] Several inhibitors of its catalytic activity are developed and some of them have proceeded to clinical trials. 9,10 We established a screening system for the inhibitors of PBD-dependent binding.…”
mentioning
confidence: 99%
“…Recent studies have also reported that PRC1 acts as a docking site for Plk1 in a phosphorylationdependent manner [7,21]. Given that HSF2 and PRC1 interact in the early stages of mitosis, an intriguing question for future studies would be to determine if HSF2 acts in a similar manner to bring PRC1 into proximity with an as yet undetermined binding partner.…”
Section: Discussionmentioning
confidence: 99%